CONVERGENCE AND MEDITERRANEAN CAPITALISM: SOME EMPIRICAL EVIDENCES ON THE LIBERALIZATION OF THE ITALIAN ECONOMIC SYSTEM - Arcidiacono, Davide (European Scientific Journal, ESJ, 2014)
In the years of the recent economic crisis, liberalization policies has taken on a new prominence in the public debate, especially in Southern European countries. However, The liberalization policies are confronted with very different institutional environments in which the action of European convergence does not cause the same effects in all countries, because it graft with structure, rules and heterogeneous cultures that determine "multiple equilibria" affected by processes of path dependence. The belonging to the Mediterranean model of Capitalism helps to explain the slowness and limits of a top down liberalization process that is not coherent with country’s corporate and familist culture. Therefore, the social costs of liberalization policies are higher than the expected benefits where the processes of institutional reform are not accompanied by a high level of coordination and legitimation among the actors involved. The analysis of the Italian case highlights the failure of the process of convergence in a Mediterranean country, where the role of informal ties and the low level of institutional cooperation, generate imbalances in the regulatory structure of the economic system, rather than generating a virtuous circle in terms of efficiency and customer satisfaction. Empowering consumer’s action through transparency policies would be an effective contrast to the action of pressure exercised by some corporate business groups that has heavily influenced the history of the Italian liberalization.